The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1128/jb.138.2.510-518.1979
|View full text |Cite
|
Sign up to set email alerts
|

Transformation-derived Neisseria gonorrhoeae plasmids with altered structure and function

Abstract: Plasmid deoxyribonucleic acid from Neisseria gonorrhoeae containing a 7.1kilobase (kb) (4.7-megadalton) penicillinase (Pcr) plasmid transformed homogenic gonococci to penicillinase production at a low frequency. About 25% of the penicillinase-producing gonococcal transformants contained Pc' plasmids which were either larger or smaller than the 7.1 kb donor plasmid; these Pcr plasmids varied in size from 3.45 to 42 kb. Some of these altered plasmids differed from the donor plasmid in stability or in frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 32 publications
3
30
1
Order By: Relevance
“…This was confirmed by further analysis which showed that these plasmids contain a 1.6 kb fragment closely related to the /3-1actamase coding region of the Tn 3-like transposon Tn2301 [14,15]. The 7.4 kb plasmids reported here are probably identical to the 7.1 kb plasmids described by others [1,3].…”
Section: Plasmid Content Of the Three Gonococcal Strains And Identifisupporting
confidence: 87%
See 1 more Smart Citation
“…This was confirmed by further analysis which showed that these plasmids contain a 1.6 kb fragment closely related to the /3-1actamase coding region of the Tn 3-like transposon Tn2301 [14,15]. The 7.4 kb plasmids reported here are probably identical to the 7.1 kb plasmids described by others [1,3].…”
Section: Plasmid Content Of the Three Gonococcal Strains And Identifisupporting
confidence: 87%
“…Two types of R plasmids have been found in N. gonorrhoeae: one is 5.1 kilobase pairs (kb) long and the other 7.1 kb. They are closely related as judged by their high degree of homology [1,3]. In view of the medical significance of this resistance, it is of interest from an epidemiological point of view to analyse newly isolated gonococcal Amp r strains and to determine the genetic basis of their resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of gonococci to penicillin increased slowly over many years, but treatment failure could be prevented by suitably increased doses of penicillin. This resistance was chromosomal and non-enzymic; in 1976, however, plasmids determining the production of the TEM 1 ,-lactamase appeared in gonococci (12)(13)(14)(15), which then exhibited total resistance to penicillin. (For reviews of the development of resistance in gonococci, see references [16][17][18].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…A single restriction endonuclease BamHI cleavage site is present within the tnpR gene. The Ampr gonococcal plasmids contain this BamHI site, which is situated in the part homologous to Tn2 (23).…”
mentioning
confidence: 99%